2014
DOI: 10.1007/s12070-014-0802-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prognosis of Deep Neck Infections

Abstract: Deep neck infections could have serious threats for life of patients, if not noticed adequately. Early diagnosis and correct treatment planning can save the patient's lives and prevent complications of disease extension and also surgical procedures that in some instances may be performed in an emergent situation with higher complication rates. Herein, we have studied 815 cases of deep neck abscesses and infections with especial consideration to treatment and prognosis. In a retrospective case review, we studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 12 publications
3
37
1
3
Order By: Relevance
“…In the study conducted by Yang et al, CKD constituted the third most common condition predisposing to DNIs following DM and nasopharyngeal cancer after radiotherapy [58]. Motahari et al observed that ESKD was defined as a condition precipitating DNIs in 3.1% of all DNIs cases [59].…”
Section: Deep Neck Infections (Dnis)mentioning
confidence: 99%
“…In the study conducted by Yang et al, CKD constituted the third most common condition predisposing to DNIs following DM and nasopharyngeal cancer after radiotherapy [58]. Motahari et al observed that ESKD was defined as a condition precipitating DNIs in 3.1% of all DNIs cases [59].…”
Section: Deep Neck Infections (Dnis)mentioning
confidence: 99%
“…However, treatment of a neck abscess usually requires, in addition to appropriate antibiotic therapy, surgical drainage of the abscess,2 3 with earlier surgery associated with better outcome 1…”
Section: Introductionmentioning
confidence: 99%
“…Requiere de un enfrentamiento rápido y ordenado, con énfasis en la evaluación de la permeabilidad de vía aérea. Si bien el manejo debe ser adaptado caso a caso, se recomienda hospitalizar al paciente, debido a la evolución incierta de este cuadro, pudiendo presentar un compromiso de vía aérea rápidamente progresivo requiriendo inclusive traqueotomía o cricotiroidotomía de urgencia 10 .…”
Section: Introductionunclassified
“…Se describen numerosas complicaciones de un ARF y de los abscesos profundos del cuello, entre ellos obstrucción de vía aérea, mediastinitis, osteomielitis de los cuerpos vertebrales, fasceitis necrotizante, entre otros, que si bien suelen ser poco frecuentes, pueden poner en riesgo la vida del paciente 4,10,11 .…”
Section: Introductionunclassified